Cubic boron nitride sintered body and coated cubic nitride sintered body
The optimized cubic nitride sintered bodies with specific CBN, Ti, Al, and W phase ratios and a coating layer address the limitations of thermal conductivity and toughness, resulting in extended tool life and improved performance in cutting tools.
Patent Information
- Application Number
- JP2023118933
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2043-07-21
AI Technical Summary
Cubic nitride sintered bodies containing a Ti compound have low thermal conductivity and toughness, which limits their effectiveness in cutting tools, especially in high-speed and deep-cut applications.
A specific configuration of cubic nitride sintered bodies is developed, comprising 10.0% to 60.0% CBN, 40.0% to 90.0% binding phase, with optimized ratios of Ti, Al, and W phases, and a coating layer, enhancing mechanical strength, thermal conductivity, and wear resistance.
The improved cubic nitride sintered bodies exhibit extended tool life with enhanced abrasion resistance and toughness, suitable for high-speed cutting tools.
Smart Images

Figure 2025015975000001 
Figure 2025015975000002 
Figure 2025015975000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a cubic boron nitride sintered body and a coated cubic boron nitride sintered body. [Background technology]
[0002] Cubic boron nitride sintered compacts contain cubic boron nitride (hereinafter also referred to as "cBN") and a binder phase. For tools using cBN sintered compacts for cutting ferrous workpieces such as steel and cast iron, cBN sintered compacts containing Ti compounds as binder phase materials have traditionally been widely used. This is because cBN sintered compacts containing Ti compounds have low affinity with ferrous workpieces and have excellent reactive wear resistance.
[0003] For this reason, cBN sintered bodies containing various Ti compounds have been proposed in recent years. For example, Patent Document 1 discloses a cBN-based ultra-high pressure sintered body containing cBN particles and a binder phase, in which the binder phase contains at least one of an Al nitride or oxide, or a Ti nitride, carbide, or carbonitride, and in which 0.1 to 5.0 volume % of metal borides having an average particle size of 20 to 300 nm are dispersed, and the metal borides contain at least one of Nb, Ta, Cr, Mo, and W as a metal component, but do not contain Ti. A cBN-based ultra-high-pressure sintered body has been proposed, which contains a boride (B) and a metal boride (A) whose metal component contains only Ti, and in which, when the proportion (volume %) of the metal boride (A) containing only Ti as a metal component among the metal borides is Va and the proportion (volume %) of the metal boride (B) containing at least one of Nb, Ta, Cr, Mo, and W as a metal component but not Ti is Vb, the ratio Vb / Va is 0.1 to 1.0.
[0004] Furthermore, for example, Patent Document 2 discloses a cubic boron nitride-based ultra-high pressure sintered cutting tool having a tool substrate made of a cubic boron nitride-based ultra-high pressure sintered compact containing cubic boron nitride particles, a binder phase, a Ti boride phase, and a W boride phase, in which the cubic boron nitride particles have an average particle size of 0.5 to 3.5 μm and a content of 40 to 75% by volume, and in which fine Ti boride phases having an average particle size of 50 to 500 nm and fine W boride phases having an average particle size of 50 to 500 nm are dispersed and distributed in the binder phase, the sum of the amounts of the fine Ti boride phase and the W boride phase produced is 5 to 15% by volume of the binder phase, 15 to 35% by volume of the binder phase is at least one or more of Al nitrides and oxides, and the remainder is at least one or more of Ti nitrides, carbides, borides, and carbonitrides, as well as unavoidable impurities, and 0.5≦(Amount of W boride phase formed) / (Amount of Ti boride phase formed)≦1.0 There has been proposed a cutting tool made of a cubic boron nitride based ultra-high pressure sintered compact, characterized in that the tool substrate is made of a cubic boron nitride based ultra-high pressure sintered compact that satisfies the relationship of (a) above. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 175598 [Patent Document 2] Japanese Patent Application Laid-Open No. 2014-083664 Summary of the Invention [Problem to be solved by the invention]
[0006] However, cubic boron nitride sintered bodies containing Ti compounds have low thermal conductivity and toughness, and there is room for improvement. In recent years, there has been a demand for higher efficiency in cutting processes, with speeds, feed rates, and depths of cut becoming more pronounced. For this reason, cutting processes in recent years have required tools with improved chipping resistance and wear resistance compared to conventional methods.
[0007] In light of this, the cBN-based ultra-high pressure sintered compact described in Patent Document 1 has insufficient thermal conductivity and leaves room for improvement in wear resistance. Also, the cubic boron nitride-based ultra-high pressure sintered compact cutting tool described in Patent Document 2 has a binder phase that contains a large proportion of Al2O3, which has poor thermal conductivity, and / or AlN, which has poor mechanical strength, leaving room for improvement in wear resistance and / or fracture resistance.
[0008] An object of the present invention is to provide a cubic boron nitride sintered body and a coated cubic boron nitride sintered body that have excellent wear resistance and chipping resistance, thereby enabling an extension of tool life. [Means for solving the problem]
[0009] The present inventors have conducted extensive research into extending tool life and have discovered that when a cubic boron nitride sintered body has a specific structure, it is possible to improve its wear resistance and fracture resistance, thereby extending tool life, which has led to the completion of the present invention.
[0010] The gist of the present invention is as follows. [1] A cubic boron nitride sintered body comprising cubic boron nitride and a binder phase, the content of the cubic boron nitride is 10.0% by volume or more and 60.0% by volume or less, and the content of the binder phase is 40.0% by volume or more and 90.0% by volume or less, relative to 100.0% by volume of the entire cubic boron nitride sintered body; the binder phase includes a Ti compound phase, an Al compound phase, and a phase containing a W element, With respect to 100.0% by volume of the entire binder phase, the content of the Ti compound phase is 60.0% by volume or more and 92.0% by volume or less, the content of the Al compound phase is more than 0.0% by volume and less than 15.0% by volume, and the content of the phase containing W element is 5.0% by volume or more and 30.0% by volume or less, the phase containing the W element includes at least one selected from the group consisting of WB and WB, A cubic boron nitride sintered body, wherein I2 / I1 is 0.03 or more and 0.60 or less, where I1 is the X-ray diffraction peak intensity of the (111) plane of the cubic boron nitride and I2 is the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase. [2] The cubic boron nitride sintered body according to [1], wherein when the X-ray diffraction peak intensity of the (101) plane of WB2 in the binder phase is I3, I3 / I1 is 0.03 or less. [3] The cubic boron nitride sintered body according to [1] or [2], wherein, when the X-ray diffraction peak intensity of the (211) plane of W2B in the binder phase is I4, I4 / I2 is 0.50 or more and 0.95 or less. [4] The cubic boron nitride sintered body according to any one of [1] to [3], wherein the phase containing the W element has an average thickness λ of 0.03 μm or more and 0.12 μm or less. [5] the Ti compound phase contains TiB2, The cubic boron nitride sintered body according to any one of [1] to [4], wherein, when the X-ray diffraction peak intensity of the (101) plane of TiB2 in the binder phase is I5, I5 / I1 is 0.07 or more and 0.55 or less. [6] the phase containing the W element contains the Co element, The cubic boron nitride sintered body according to any one of [1] to [5], wherein in the phase containing W element, the content of Co element relative to the total content of W element and Co element is 5 atomic % or more and less than 50 atomic %. [7] [1] to [6], and a coating layer formed on the surface of the cubic boron nitride sintered body, A coated cubic boron nitride sintered body, wherein the average thickness of the entire coating layer is 0.5 μm or more and 6.0 μm or less. [Effects of the Invention]
[0011] According to the present invention, it is possible to provide a cubic boron nitride sintered body and a coated cubic boron nitride sintered body that have excellent wear resistance and chipping resistance, thereby enabling an extension of tool life. DETAILED DESCRIPTION OF THE INVENTION
[0012] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail, but the present invention is not limited to the following embodiment. The present invention can be modified in various ways without departing from the gist of the present invention.
[0013] The cBN sintered body of this embodiment is a cBN sintered body containing cBN and a binder phase, and the cBN content is 10.0 volume % or more and 60.0 volume % or less, and the binder phase content is 40.0 volume % or more and 90.0 volume % or less, relative to 100.0 volume % of the entire cBN sintered body. The binder phase includes a Ti compound phase, an Al compound phase, and a phase containing W element, and the Ti compound phase content is 60.0 volume % or more and 92.0 volume % or less, relative to 100.0 volume % of the entire binder phase. the content of the Al compound phase is more than 0.0 vol% and less than 15.0 vol%, the content of the phase containing W element is 5.0 vol% or more and 30.0 vol% or less, the phase containing W element includes at least one selected from the group consisting of W2B and WB, and when I1 is the X-ray diffraction peak intensity of the (111) plane of cBN and I2 is the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase, I2 / I1 is 0.03 or more and 0.60 or less.
[0014] By adopting such a configuration, the cBN sintered body of this embodiment can improve the wear resistance and chipping resistance, and as a result, the tool life can be extended. The factors that enable the cBN sintered body of this embodiment to have improved wear resistance and fracture resistance and a long tool life are not fully understood, but the inventors believe that the factors are as follows. However, the factors are not limited to these. Specifically, the cBN sintered body of this embodiment has a cBN content of 10.0 volume % or more relative to the total volume of the cBN sintered body (100.0 volume %), which results in a high content of cBN, which has excellent mechanical strength, and therefore excellent fracture resistance. On the other hand, the cBN sintered body of this embodiment has a cBN content of 60.0 volume % or less, which results in a low content of cBN, which has poor resistance to reactivity with iron, and therefore excellent wear resistance. Furthermore, the cBN sintered body of this embodiment has a binder phase content of 40.0 volume % or more, which results in a relatively low content of cBN, which has poor resistance to reactivity with iron, and therefore excellent wear resistance. On the other hand, the cBN sintered body of this embodiment has a binder phase content of 90.0 vol% or less, which results in a relatively high content of cBN, which has excellent mechanical strength, and therefore has excellent fracture resistance. Furthermore, the cBN sintered body of this embodiment has a Ti compound phase content of 60.0 vol% or more relative to 100.0 vol% of the entire binder phase, which improves resistance to reactivity with iron, and therefore has excellent wear resistance. On the other hand, the cBN sintered body of this embodiment has a Ti compound phase content of 92.0 vol% or less, which improves thermal conductivity, and therefore has excellent wear resistance. Furthermore, the cBN sintered body of this embodiment has an Al compound phase content of more than 0.0 vol% relative to 100.0 vol% of the entire binder phase, which improves sinterability, and therefore has excellent fracture resistance. On the other hand, the cBN sintered body of this embodiment has an Al compound phase content of less than 15.0% by volume, which reduces the content of Al compounds (e.g., Al2O3) with poor thermal conductivity and / or the content of Al compounds (e.g., AlN) with poor mechanical strength, resulting in excellent wear resistance and / or fracture resistance. Furthermore, the Al compound phase content of less than 15.0% by volume can prevent the W-containing phase from forming an agglomerated structure, and the W-containing phase is uniformly distributed in the binder phase, improving the thermal conductivity of the cBN sintered body, thereby primarily resulting in excellent wear resistance.Furthermore, the cBN sintered body of this embodiment has an improved thermal conductivity due to the W-containing phase being 5.0 vol% or more relative to the total binder phase (100.0 vol%). This improves the hardness of the cBN sintered body, resulting in excellent wear resistance. The W-containing phase is 30.0 vol% or less, resulting in excellent hardness. The cBN sintered body of this embodiment also has an improved wear resistance. The W-containing phase of this embodiment includes at least one selected from the group consisting of W2B and WB. When the X-ray diffraction peak intensity of the (111) plane of cBN is I1 and the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase is I2, the ratio I2 / I1 is 0.03 or more, resulting in improved thermal conductivity. The cBN sintered body of this embodiment also has an improved toughness due to the I2 / I1 ratio being 0.60 or less, resulting in improved fracture resistance. These effects work together to provide the cBN sintered body of this embodiment with improved wear resistance and chipping resistance, resulting in a long tool life.
[0015] The cBN sintered body of this embodiment contains cBN and a binder phase. The cBN content is 10.0 volume % or more and 60.0 volume % or less, and the binder phase content is 40.0 volume % or more and 90.0 volume % or less. In the cBN sintered body of this embodiment, the total content of cBN and the binder phase is 100.0 volume %.
[0016] The cBN sintered body of this embodiment has a cBN content of 10.0% by volume or more, which results in a high content of cBN, which has excellent mechanical strength, and therefore excellent chipping resistance. On the other hand, the cBN sintered body of this embodiment has a cBN content of 60.0% by volume or less, which results in a low content of cBN, which has poor resistance to reactivity with iron, and therefore excellent wear resistance. From the same perspective, the cBN content is preferably 12.2% by volume or more and 57.2% by volume or less, and more preferably 25.1% by volume or more and 45.2% by volume or less.
[0017] Furthermore, the cBN sintered body of this embodiment has a binder phase content of 40.0 vol% or more, which results in a relatively low content of cBN, which has poor reactivity with iron, and therefore excellent wear resistance. On the other hand, the cBN sintered body of this embodiment has a binder phase content of 90.0 vol% or less, which results in a relatively high content of cBN, which has excellent mechanical strength, and therefore excellent fracture resistance. From the same perspective, the binder phase content is preferably 42.8 vol% to 87.8 vol%, and more preferably 54.8 vol% to 74.9 vol%.
[0018] In the cBN sintered body of this embodiment, the content (vol %) of cBN and binder phase can be determined by photographing an arbitrary cross section with a scanning electron microscope (SEM) and analyzing the SEM photograph with commercially available image analysis software. Specifically, it can be determined by the method described in the Examples below.
[0019] In the cBN sintered body of this embodiment, the binder phase includes a Ti compound phase, an Al compound phase, and a phase containing W element. In this embodiment, the content of the Ti compound phase is 60.0 vol% or more and 92.0 vol% or less, relative to 100.0 vol% of the entire binder phase. The cBN sintered body of this embodiment has excellent wear resistance because the Ti compound phase content is 60.0 vol% or more, improving its resistance to reactivity with iron. Meanwhile, the cBN sintered body of this embodiment has excellent wear resistance because the Ti compound phase content is 92.0 vol% or less, improving its thermal conductivity. From the same perspective, the Ti compound phase content is preferably 65.5 vol% or more and 91.2 vol% or less, and more preferably 73.4 vol% or more and 88.8 vol% or less.
[0020] In the cBN sintered body of this embodiment, the Ti compound phase preferably contains at least one selected from the group consisting of TiC, TiCN, TiN, and TiB2. When the Ti compound phase contains such a compound, it tends to have excellent reactive wear resistance. From the same viewpoint, the Ti compound phase more preferably contains at least one selected from the group consisting of TiC, TiCN, and TiB2, and even more preferably contains at least one selected from the group consisting of TiC and TiB2.
[0021] In the cBN sintered body of this embodiment, the content of the Al compound phase is greater than 0.0 vol% and less than 15.0 vol%, based on 100.0 vol% of the entire binder phase. The cBN sintered body of this embodiment has excellent fracture resistance due to improved sinterability due to the Al compound phase content greater than 0.0 vol%. On the other hand, the cBN sintered body of this embodiment has excellent wear resistance and / or fracture resistance due to a reduced content of Al compounds with poor thermal conductivity (e.g., Al2O3) and / or Al compounds with poor mechanical strength (e.g., AlN). Furthermore, the Al compound phase content less than 15.0 vol% can prevent the formation of an agglomerated structure of the W-containing phase. Furthermore, the W-containing phase is uniformly distributed throughout the binder phase, improving the thermal conductivity of the cBN sintered body and resulting in excellent wear resistance. From the same viewpoint, the content of the Al compound phase is preferably 2.0% by volume or more and 14.2% by volume or less, and more preferably 2.9% by volume or more and 11.5% by volume or less.
[0022] In the cBN sintered body of this embodiment, the Al compound phase preferably contains at least one selected from the group consisting of Al2O3, AlN, and AlB2. When the Al compound phase contains such a compound, the sinterability of the cBN sintered body improves, and therefore the cBN sintered body tends to have excellent fracture resistance. From the same viewpoint, the Al compound phase more preferably contains at least one selected from the group consisting of Al2O3 and AlN, and even more preferably contains Al2O3.
[0023] In the cBN sintered body of this embodiment, the content of the phase containing W element is 5.0 vol% or more and 30.0 vol% or less, relative to 100.0 vol% of the entire binder phase. Since the content of the phase containing W element is 5.0 vol% or more, the cBN sintered body of this embodiment has improved thermal conductivity and therefore excellent wear resistance. Meanwhile, since the content of the phase containing W element is 30.0 vol% or less, the cBN sintered body of this embodiment has improved hardness and therefore excellent wear resistance. From the same perspective, the content of the phase containing W element is preferably 5.9 vol% or more and 28.4 vol% or less, and more preferably 8.1 vol% or more and 20.5 vol% or less. In this embodiment, the content (volume %) of the Ti compound phase, the Al compound phase, and the phase containing W element in the binder phase can be measured by the method described in the examples below.
[0024] In the cBN sintered compact of this embodiment, the W-containing phase may contain, in addition to the above-mentioned WB and WB, at least one selected from the group consisting of metal, carbides, nitrides, borides, and solid solutions thereof, and alloys containing W and at least one selected from the group consisting of Co, Al, Ti, Ni, V, Cr, Zr, Nb, Mo, Hf, and Ta, as well as carbides, nitrides, borides, and solid solutions thereof. When the W-containing phase contains such materials, the bond strength between particles in the cBN sintered compact is improved, and chipping resistance tends to be excellent.
[0025] In the cBN sintered compact of this embodiment, the phase containing W preferably contains Co. When the phase containing W contains Co, the bond strength between particles in the cBN sintered compact is improved, and toughness is also improved, so that the cBN tends to have excellent fracture resistance. In this embodiment, when there are multiple phases containing W element, the phrase "phases containing W element contain Co element" includes not only the case where all of the phases containing W element contain Co element, but also the case where only some of the phases containing W element contain Co element. The compound containing W and Co elements is not particularly limited, but may be, for example, CoW2B2. When the W-containing phase contains Co, the content of Co relative to the total content of W and Co is preferably 5 atomic % or more and less than 50 atomic %. The cBN sintered body of this embodiment has improved toughness and therefore tends to have better fracture resistance because the W-containing phase has a Co content of 5 atomic % or more relative to the total content of W and Co. On the other hand, the cBN sintered body of this embodiment has improved hardness and therefore tends to have better wear resistance because the W-containing phase has a Co content of less than 50 atomic % relative to the total content of W and Co. From the same perspective, the Co content relative to the total content of W and Co is more preferably 6 atomic % or more and 43 atomic % or less, and even more preferably 9 atomic % or more and 33 atomic % or less. In this embodiment, the content (atomic %) of Co element in the phase containing W element can be measured by the method described in the examples below.
[0026] In the cBN sintered body of this embodiment, the average thickness λ of the W-containing phase is preferably 0.03 μm or more and 0.12 μm or less. In the cBN sintered body of this embodiment, the average thickness λ of the W-containing phase is 0.03 μm or more, which improves the toughness of the binder phase and tends to further improve fracture resistance. On the other hand, in the cBN sintered body of this embodiment, the average thickness λ of the W-containing phase is 0.12 μm or less, which indicates that the W-containing phase has little agglomerated structure and is uniformly distributed throughout the binder phase, improving thermal conductivity and therefore tends to further improve wear resistance. From the same perspective, the average thickness λ of the W-containing phase is more preferably 0.04 μm or more and 0.11 μm or less, and even more preferably 0.05 μm or more and 0.10 μm or less. In this embodiment, the average thickness λ of the phase containing W element can be measured by the method described in the examples below.
[0027] In the cBN sintered body of this embodiment, the W-containing phase includes at least one selected from the group consisting of W2B and WB. When I1 is the X-ray diffraction peak intensity of the (111) plane of cBN and I2 is the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase, I2 / I1 is 0.03 or more and 0.60 or less. Since the cBN sintered body of this embodiment has an I2 / I1 ratio of 0.03 or more, the thermal conductivity is improved, resulting in excellent wear resistance. Meanwhile, since the cBN sintered body of this embodiment has an I2 / I1 ratio of 0.60 or less, the toughness is improved, resulting in improved fracture resistance. From the same viewpoint, I2 / I1 is preferably 0.04 or more and 0.56 or less, more preferably 0.06 or more and 0.54 or less, and even more preferably 0.08 or more and 0.52 or less.
[0028] In the cBN sintered body of this embodiment, when the X-ray diffraction peak intensity of the (111) plane of cBN is I1 and the X-ray diffraction peak intensity of the (101) plane of WB2 in the binder phase is I3, the ratio I3 / I1 is preferably 0.03 or less. In the cBN sintered body of this embodiment, an I3 / I1 ratio of 0.03 or less indicates that the formation of hexagonal W borides, which have low mechanical strength, is suppressed, improving toughness and tending to provide even more excellent fracture resistance. From the same perspective, I3 / I1 is more preferably 0.02 or less, even more preferably 0.01 or less, and even more preferably 0.00. In the cBN sintered body of this embodiment, it is preferable that the W-containing phase does not substantially contain WB2. In this embodiment, "substantially free of WB2" means that WB2 is not detected in the bonded phase by X-ray diffraction measurement.
[0029] In the cBN sintered body of this embodiment, when the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase is I2 and the X-ray diffraction peak intensity of the (211) plane of W2B in the binder phase is I4, the ratio I4 / I2 is preferably 0.50 or more and 0.95 or less. When the cBN sintered body of this embodiment has an I4 / I2 ratio of 0.50 or more, the thermal conductivity is improved, and therefore the wear resistance tends to be even more excellent. On the other hand, when the cBN sintered body of this embodiment has an I4 / I2 ratio of 0.95 or less, the hardness is improved, and therefore the wear resistance tends to be even more excellent. From the same viewpoint, the ratio I4 / I2 is more preferably 0.51 or more and 0.94 or less, and even more preferably 0.57 or more and 0.92 or less.
[0030] In the cBN sintered body of this embodiment, the Ti compound phase contains TiB2, and when I1 is the X-ray diffraction peak intensity of the (111) plane of cBN and I5 is the X-ray diffraction peak intensity of the (101) plane of TiB2 in the binder phase, the ratio I5 / I1 is preferably 0.07 or more and 0.55 or less. The cBN sintered body of this embodiment contains TiB2, and the ratio I5 / I1 is 0.07 or more, which improves the bonding strength between the cBN and the binder phase, thereby tending to have even better fracture resistance. On the other hand, the cBN sintered body of this embodiment has an I5 / I1 ratio of 0.55 or less, which reduces the proportion of TiB2, which has low mechanical strength, thereby improving toughness and tending to have even better fracture resistance. From the same perspective, the ratio I5 / I1 is preferably 0.08 or more and 0.53 or less, and more preferably 0.09 or more and 0.42 or less.
[0031] In this embodiment, the composition of the binder phase can be identified using a commercially available X-ray diffractometer. For example, the composition of the binder phase can be identified by performing X-ray diffraction measurement using a 2θ / θ focusing optical system with Cu-Kα radiation using an X-ray diffractometer manufactured by Rigaku Corporation (product name "SmartLab") under the following conditions. The measurement conditions are as follows: Output: 45kV, 200mA, Entrance side Soller slit: 5°, Divergence vertical slit: 2 / 3°, Divergence vertical limit slit: 5 mm, Scattering slit 2 / 3°, Solar slit on light receiving side: 5°, Receiving slit: 0.3 mm, Sampling width: 0.02°, Scan speed: 1° / min, The 2θ measurement range is preferably 30 to 90°. In this embodiment, the composition of the binder phase can be measured by the method described in the examples below.
[0032] In this embodiment, the X-ray diffraction peak intensities of the cBN and each compound in the binder phase can be measured using a commercially available X-ray diffractometer. For example, the X-ray diffraction peak intensities can be measured using an X-ray diffractometer (product name "SmartLab") manufactured by Rigaku Corporation. Examples of measurement conditions are the same as those used in the method for identifying the composition of the binder phase described above.
[0033] The cBN sintered body of this embodiment may unavoidably contain impurities. Examples of impurities include, but are not limited to, lithium contained in the raw material powder. Typically, the content of unavoidable impurities is 1 mass% or less of the entire cBN sintered body. Therefore, the unavoidable impurities have almost no effect on the characteristics of the cBN sintered body.
[0034] The coated cBN sintered body of this embodiment includes the above-described cBN sintered body and a coating layer formed on the surface of the cBN sintered body. Forming a coating layer on the surface of the cBN sintered compact further improves the wear resistance of the cBN sintered compact. The coating layer preferably contains at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, and Si, and at least one element selected from the group consisting of C, N, O, and B. The coating layer may have a single-layer structure or a laminated structure including two or more layers. When the coating layer has such a structure, the coated cBN sintered compact of this embodiment has even further improved wear resistance.
[0035] The method for producing the coating layer in the coated cBN sintered compact of this embodiment is not particularly limited, but examples include chemical vapor deposition and physical vapor deposition methods such as ion plating, arc ion plating, sputtering, and ion mixing. Among these, arc ion plating is more preferable because it provides even better adhesion between the coating layer and the cBN sintered compact.
[0036] Examples of compounds that form the coating layer include, but are not limited to, TiN, TiC, TiCN, TiAlN, TiSiN, and CrAlN. The coating layer may have a structure in which multiple layers with different compositions are alternately stacked. In this case, the average thickness of each layer is, for example, 5 nm to 500 nm.
[0037] The average thickness of the entire coating layer is preferably 0.5 μm or more and 6.0 μm or less. When the average thickness of the entire coating layer of the coated cBN sintered body of this embodiment is 0.5 μm or more, the wear resistance tends to be improved. On the other hand, when the average thickness of the entire coating layer is 6.0 μm or less, the occurrence of defects due to peeling tends to be suppressed. From the same viewpoint, the average thickness of the entire coating layer is more preferably 1.0 μm or more and 5.5 μm or less, and even more preferably 1.0 μm or more and 5.0 μm or less.
[0038] The thickness of each layer constituting the coating layer and the thickness of the entire coating layer can be measured from the cross-sectional structure of the coated cBN sintered compact using an optical microscope, SEM, transmission electron microscope (TEM), etc. Note that, when the coating layer is formed by arc ion plating, for example, the average thickness of each layer and the average thickness of the entire coating layer can be determined by measuring the thickness of each layer and the thickness of the entire coating layer from three or more cross sections in the vicinity of a position 50 μm from the cutting edge toward the center of the surface facing the metal evaporation source, and then calculating the average value.
[0039] The composition of each layer constituting the coating layer can be measured from the cross-sectional structure of the coated cBN sintered body using EDS or wavelength dispersive X-ray analyzer (WDS).
[0040] The cBN sintered body or coated cBN sintered body of this embodiment has excellent wear resistance and fracture resistance, and is therefore preferably used as a cutting tool or a wear-resistant tool, and is particularly preferably used as a cutting tool. The cBN sintered body or coated cBN sintered body of this embodiment is even more preferably used as a cutting tool for cast iron. When the cBN sintered body or coated cBN sintered body of this embodiment is used as a cutting tool or a wear-resistant tool, the tool life can be extended compared to conventional tools.
[0041] The cBN sintered body of this embodiment can be produced, for example, by the following method. As raw material powders, cBN powder, TiC powder, TiC 0.8 Powder, TiCN powder, Ti(CN) 0.8 powder, TiN powder, TiN 0.8 Powder, WC powder, Co powder, and Al powder are prepared. Furthermore, by appropriately adjusting the ratio of each raw material powder, the content (volume %) of cBN and the binder phase in the resulting cBN sintered body can be controlled within the above-mentioned specific range. Furthermore, by appropriately adjusting the ratio of each raw material powder, the content (volume %) of the Ti compound phase, the W-containing phase, and the Al compound phase in the binder phase can be controlled within the above-mentioned specific range. Furthermore, by appropriately adjusting the ratio of each raw material powder, the content of Co element in the W-containing phase relative to the total content of W element and Co element can be controlled within the above-mentioned specific range. Next, the prepared raw material powders are placed in a ball mill cylinder along with cermet balls, a solvent, and paraffin and mixed. The raw material powder mixed in a ball mill is filled into a high-melting-point metal capsule made of Zr in a nitrogen atmosphere in a glove box. In order to remove moisture and organic components adsorbed on the surface of the filled raw material powder, a vacuum heat treatment is performed with the capsule open. After the vacuum heat treatment, the capsule is sealed, and the raw material powder filled in the capsule is sintered at high temperature and high pressure. The high-pressure sintering conditions are, for example, a pressure of 4.0 to 7.0 GPa, a temperature of 1250 to 1550°C, and a sintering time of 20 to 60 minutes.
[0042] When the X-ray diffraction peak intensity of the (111) plane of cBN is I1 and the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase is I2, there is no particular limitation on the method for controlling I2 / I1 within the above-mentioned specific range, and examples include appropriately adjusting the type and blending ratio of raw material powders, and appropriately adjusting the temperature at which the raw material powders are sintered. Specifically, examples of methods for increasing I2 / I1 include reducing the content (volume %) of cBN in the cBN sintered body, increasing the content (volume %) of the phase containing W in the binder phase, and using a compound raw material (TiC) in which the atomic ratio of metal elements to non-metal elements is non-stoichiometric in the raw material of the Ti compound phase. 0.8 , Ti(CN) 0.8 or TiN 0.8 ) and increasing its content, increasing the temperature at which the raw material powder is sintered, or further, making the content of Co element relative to the total content of W element and Co element in the W element-containing phase fall within the above-mentioned range.
[0043] When the sum of the X-ray diffraction peak intensities of the (211) plane of W2B and the (110) plane of WB in the binder phase is I2, and the X-ray diffraction peak intensity of the (211) plane of W2B in the binder phase is I4, there is no particular limitation on the method for controlling I4 / I2 within the above-mentioned specific range, and examples thereof include a method of appropriately adjusting the type and blending ratio of raw material powders, and a method of appropriately adjusting the temperature at which the raw material powders are sintered. Specifically, examples of a method for increasing I4 / I2 include increasing the content ratio of Co element relative to the total content ratio of W element and Co element in the phase containing W element, or using a compound raw material (TiC) in which the atomic ratio of metal element to non-metal element is non-stoichiometric in the raw material of the Ti compound phase. 0.8 , Ti(CN) 0.8 or TiN 0.8 ) and increasing its proportion, or lowering the temperature at which the raw material powder is sintered.
[0044] When the X-ray diffraction peak intensity of the (111) plane of cBN is I1 and the X-ray diffraction peak intensity of the (101) plane of WB2 in the binder phase is I3, the method of controlling I3 / I1 within the above-mentioned specific range is not particularly limited, but examples include a method of appropriately adjusting the type and blending ratio of raw material powders, or a method of appropriately adjusting the temperature at which the raw material powders are sintered. Specifically, a method of reducing I3 / I1 is, for example, to use a compound raw material (TiC) in which the atomic ratio of metal elements to non-metal elements in the raw material of the Ti compound phase is non-stoichiometric. 0.8 , Ti(CN) 0.8 or TiN 0.8 ) or by lowering the temperature at which the raw material powder is sintered. In addition, as a method for preventing the W-containing phase from substantially containing WB2 in the binder phase, for example, a compound raw material (TiC) in which the atomic ratio of the metal element to the nonmetal element is non-stoichiometric in the raw material of the Ti compound phase is used. 0.8 , Ti(CN) 0.8 or TiN 0.8 ) in a specific amount or more, and the temperature for sintering the raw material powder is set to 1500°C or less. Specifically, for example, a compound raw material (TiC 0.8 , Ti(CN)0.8 or TiN 0.8 ) is 50% by volume or more relative to 100% by volume of the total raw materials of the Ti compound phase, and the temperature for sintering the raw material powder is 1500°C or less, there is a tendency that the W-containing phase in the binder phase can be made to be substantially free of WB2.
[0045] When the X-ray diffraction peak intensity of the (111) plane of cBN is I1 and the X-ray diffraction peak intensity of the (101) plane of TiB2 in the binder phase is I5, there are no particular limitations on the method for controlling I5 / I1 within the above specific range, including, for example, appropriately adjusting the type and blending ratio of raw material powders, or the temperature at which the raw material powders are sintered.Specifically, methods for increasing I5 / I1 include, for example, decreasing the cBN content (volume %) in the cBN sintered compact, increasing the Ti compound phase content (volume %) in the binder phase, or increasing the temperature at which the raw material powders are sintered.
[0046] The method for controlling the average thickness λ (μm) of the W-containing phase within the above-mentioned specific range is not particularly limited, and examples thereof include a method of appropriately adjusting the type and blending ratio of raw material powders.Specifically, examples of a method for reducing the average thickness λ (μm) of the W-containing phase include a method of reducing the content (volume %) of the Al compound phase in the binder phase, and a method of increasing the content ratio of Co element in the W-containing phase relative to the total content ratio of W element and Co element.
[0047] Furthermore, in the phase containing W element, when the content ratio of Co element relative to the total content ratio of W element and Co element is increased, the content ratio of CoW2B2 tends to increase to a level that can be detected by X-ray diffraction measurement.
[0048] Furthermore, the cBN sintered body of this embodiment can be machined into a predetermined shape using a wire electric discharge machine, a laser cutting machine, or the like to manufacture a cutting tool or a wear-resistant tool including the cBN sintered body. [Example]
[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0050] Example 1 [Preparation of raw powder] cBN powder, TiC powder, TiC 0.8 Powder, TiCN powder, Ti(CN) 0.8 powder, TiN powder, TiN 0.8 The powder, WC powder, Co powder, and Al powder were mixed in the ratios shown in Table 2 below. The average particle size of each raw material powder was as shown in Table 1. The average particle size of the raw material powder was measured by the Fisher method (Fisher Sub-Sieve Sizer (FSSS)) specified in the American Society for Testing and Materials (ASTM) standard B330.
[0051] [Table 1]
[0052] [Table 2]
[0053] [Mixing raw powders] The raw material powder was placed in a cylinder for a ball mill together with cermet balls, hexane solvent, and paraffin, and mixed for 6 hours.
[0054] [Filling process and drying process] The mixed raw material powder was filled into a high-melting-point metal capsule made of Zr (hereinafter simply referred to as "capsule") in a nitrogen atmosphere in a glove box. In order to remove moisture and organic components adsorbed on the surface of the filled raw material powder, a vacuum heat treatment was carried out with the capsule open. After the vacuum heat treatment, the capsule was sealed.
[0055] [Sintering process] The raw material powder packed in the capsule was then sintered under high temperature and high pressure. The high pressure sintering conditions are shown in Table 3 below.
[0056] [Table 3]
[0057] [SEM image analysis] The cBN and binder phase contents (volume %) of cBN sintered compacts obtained by high-pressure sintering were determined by analyzing microstructure photographs of the cBN sintered compacts taken with a scanning electron microscope (SEM) using commercially available image analysis software. More specifically, the cBN sintered compacts were mirror-polished in a direction perpendicular to their surfaces. Next, backscattered electron images of the mirror-polished surfaces of the cBN sintered compacts were observed using the SEM. The mirror-polished surfaces of the cBN sintered compacts were magnified at a magnification selected to contain 100 to 300 cBN particles. Using an energy dispersive X-ray analyzer (EDS) attached to the SEM, the black regions were identified as cBN, and the gray and white regions were identified as the binder phase. Furthermore, within the binder phase, the dark gray regions were identified as an Al compound phase, the light gray regions as a Ti compound phase, and the white regions as a phase containing W. Then, microstructure photographs of the cross sections of the cBN were taken using the SEM. Using commercially available image analysis software, the occupied areas of cBN and the binder phase were determined from the obtained structural photographs, and the content ratios (volume %) were calculated from the occupied areas. Similarly, the content ratios (volume %) of the Ti compound phase, Al compound phase, and W element-containing phase in the binder phase were calculated from the ratio of each phase to the occupied area of the binder phase from the structural photographs. Here, the mirror-polished surface of the cBN sintered body refers to a cross section of the cBN sintered body obtained by mirror-polishing the surface or any cross section of the cBN sintered body. The mirror-polished surface of the cBN sintered body was obtained by polishing with diamond paste. The composition of the binder phase was identified using an X-ray diffractometer (product name: "SmartLab") manufactured by Rigaku Corporation. Specifically, the composition of the binder phase was identified by X-ray diffraction measurement using a 2θ / θ focusing optical system with Cu-Kα radiation under the following conditions. Output: 45kV, 200mA, Entrance side Soller slit: 5°, Divergence vertical slit: 2 / 3°, Divergence vertical limit slit: 5 mm, Scattering slit 2 / 3°, Solar slit on light receiving side: 5°, Receiving slit: 0.3 mm, Sampling width: 0.02°, Scan speed: 1° / min, 2θ measurement range: 30~90°. The results of these measurements are shown in Table 4 below. Furthermore, when the phase containing W element contained Co element, the content ratio (atomic %) of Co element relative to the total content ratio of W element and Co element was calculated as follows. First, EDS analysis was performed on the entire observation field in the same observation field as the structural photograph of the cBN sintered body taken with the SEM as described above, and the content ratios (atomic %) of W element and Co element contained in the cBN sintered body were measured. From the obtained value, the content ratio (atomic %) of Co element relative to the total content ratio of W element and Co element was calculated. The results are shown in Table 5.
[0058] [X-ray diffraction (XRD) analysis] The Ti compound phase, Al compound phase, and W-containing phase contained in the cBN sintered body obtained by the sintering process were analyzed by X-ray diffraction (XRD). The XRD analysis results for the Ti compound phase, Al compound phase, and W-containing phase are shown in Table 5 below. Table 5 shows only phases for which clear peaks were identified by X-ray diffraction measurement. Regarding the W-containing phase, EDS analysis identified the presence of a phase containing both W and Co, except for Comparative Sample 10. Furthermore, X-ray diffraction analysis failed to identify clear peaks for the W-containing phase in all samples except for Inventive Sample 12 and Comparative Sample 11. However, the presence of Co was confirmed in the W-containing phase in all samples except Comparative Sample 10, and CoW2B2 was detected in Inventive Sample 12 and Comparative Sample 11 by X-ray diffraction measurement. Therefore, it is inferred that all samples except Inventive Sample 12, Comparative Sample 10, and Comparative Sample 11 contain at least CoW2B2 in a proportion not detectable by X-ray diffraction measurement. Furthermore, from the obtained X-ray diffraction patterns, the X-ray diffraction peak intensity of the (111) plane of cBN, as well as the X-ray diffraction peak intensities of the (211) plane of W2B, the (110) plane of WB, the (101) plane of WB2, and the (101) plane of TiB2 in the binder phase were determined, and the respective ratios were calculated. The X-ray diffraction intensity ratio was determined from the ratio of peak heights. These results are shown in Table 6 below. The XRD measurements were performed using an X-ray diffractometer (product name "SmartLab") manufactured by Rigaku Corporation, with a 2θ / θ focusing optical system using Cu-Kα radiation. The measurement conditions were the same as those used in the method for identifying the composition of the bonded phase described above. The following PDF card was used to identify each peak. cBN:No.00-035-1365 W2B:No.01-089-1991 WB:No.00-006-0541 WB2:No.01-089-3928 TiB2:No.00-035-0741
[0059] [Calculation method for the average thickness λ of the phase containing W element] This was determined by combining and analyzing backscattered electron images of the cross-sectional structure with EDS analysis. The black areas in the backscattered electron images of the cross-sectional structure were identified as cBN, the dark gray areas as Al compound phases, the light gray areas as Ti compound phases, and the white areas as phases containing W element. The average thickness λ (μm) of the phase containing W element was calculated using the following formula. The results are shown in Table 7. λ=X / N L X: In the cross-sectional structure, the ratio of the area occupied by the phase containing W element to the area occupied by the entire binder phase was determined. N L : When an arbitrary straight line is drawn in the cross-sectional structure, the total number of phases containing W element that the line crosses is divided by the total length of the binder phase that the line crosses. L asked for.
[0060] [Table 4]
[0061] [Table 5]
[0062] [Table 6]
[0063] [Table 7]
[0064] [Cutting tool manufacturing] The obtained cBN sintered body was cut using a wire electric discharge machine to fit the tool shape of the insert shape specified in ISO standard CNGA120408. The cut cBN sintered body was joined to a base metal made of cemented carbide by brazing. The brazed tool was then honed to obtain a cutting tool.
[0065] [Cutting test] Using the obtained cutting tool, a cutting test was carried out under the following conditions. Work material: SCM415H carburized steel (HRC60), Workpiece shape: round bar, φ80mm x 200mm, Processing method: external turning, Cutting speed: 250m / min, Feed: 0.1mm / rev, Cutting depth: 0.1 mm, Coolant: Use (water-soluble coolant), Evaluation items: The tool life was determined when the tool flank wear width reached 0.10 mm or when it was chipped, and the machining time until the tool life was reached was measured. In addition, the damage type of the specimen where the tool flank wear width reached 0.10 mm and the tool life ended was determined as "normal wear," and the damage type of the specimen where the tool was chipped and the tool life ended was determined as "chip." The measurement results are shown in Table 8.
[0066] [Table 8]
[0067] As can be seen from the results shown in Table 8, cutting tools using the inventive cBN sintered body were superior in wear resistance and chipping resistance to cutting tools using the comparative cBN sintered body, and had a longer tool life.
[0068] Example 2 Next, as shown in Table 9, the surfaces of the cBN sintered compacts of Invention Products 2, 5, 8 and 9 obtained in Example 1 were subjected to ion bombardment treatment, and then coating layers were formed by arc ion plating. When forming the first and second layers, they were formed in this order on the surface of the cBN sintered compact. The respective treatment conditions were as follows. The composition and average thickness of the coating layer were as shown in Table 9 below. The composition of the first layer, Ti 0.50 Al 0.50 N / Ti 0.33 Al 0.67 For N, 50 nm of Ti per layer 0.50 Al 0.50 N and Ti 0.33 Al0.67 The Ti and N layers were alternately formed. 0.50 Al 0.50 N / Ti 0.33 Al 0.67 The total thickness of N was formed to be equal to the average thickness of the first layer.
[0069] [Conditions for ion bombardment treatment] Base material temperature: 500℃ Pressure: 2.7 Pa Ar gas atmosphere Voltage: -400V Current: 40A Time: 30 minutes
[0070] [Coating layer formation conditions] Base material temperature: 500℃ Pressure: 3.0 Pa nitrogen (N2) gas atmosphere (nitride layer), or 3.0 Pa nitrogen (N2) gas and acetylene (C2H2) gas mixed gas atmosphere (carbonitride layer) Voltage: -60V Current: 120A
[0071] [Table 9]
[0072] Using the coated cBN sintered body having the coating layer formed on the surface, a cutting test was carried out in the same manner as in Example 1. The results are shown in Table 10 below.
[0073] [Table 10]
[0074] As can be seen from the results shown in Table 10, the coated cBN sintered compacts (Invention Products 26 to 45) on whose surfaces a coating layer was formed had even better wear resistance and longer tool life than the cBN sintered compacts (Invention Products 1 to 25) on which no coating layer was formed. [Industrial Applicability]
[0075] The cBN sintered body and coated cBN sintered body of the present invention have excellent wear resistance and fracture resistance, and can extend the tool life compared to conventional tools, and in that respect they have high industrial applicability.
Claims
1. A cubic boron nitride sintered body comprising cubic boron nitride and a binder phase, the content of the cubic boron nitride is 10.0 vol% or more and 60.0 vol% or less, and the content of the binder phase is 40.0 vol% or more and 90.0 vol% or less, relative to 100.0 vol% of the entire cubic boron nitride sintered body; the binder phase includes a Ti compound phase, an Al compound phase, and a phase containing a W element, With respect to 100.0 vol% of the entire binder phase, the content of the Ti compound phase is 60.0 vol% or more and 92.0 vol% or less, the content of the Al compound phase is more than 0.0 vol% and less than 15.0 vol%, and the content of the phase containing W element is 5.0 vol% or more and 30.0 vol% or less, The phase containing the W element is W 2 At least one selected from the group consisting of B and WB, The X-ray diffraction peak intensity of the (111) plane of the cubic boron nitride is I 1 and W in the binder phase 2 The sum of the X-ray diffraction peak intensities of the (211) plane of WB and the (110) plane of WB is I 2 Then, I 2 / I 1 is 0.03 or more and 0.60 or less.
2. WB in the bonded phase 2 The X-ray diffraction peak intensity of the (101) plane of 3 Then, I 3 / I 1 The cubic boron nitride sintered body according to claim 1 , wherein is 0.03 or less.
3. W in the binder phase 2 The X-ray diffraction peak intensity of the (211) plane of B is I 4 Then, I 4 / I 2 The cubic boron nitride sintered body according to claim 1 , wherein is 0.50 or more and 0.95 or less.
4. 2. The cubic boron nitride sintered body according to claim 1, wherein the average thickness λ of the phase containing W element is 0.03 μm or more and 0.12 μm or less.
5. The Ti compound phase is TiB 2 Including, TiB in the binder phase 2 The X-ray diffraction peak intensity of the (101) plane of 5 Then, I 5 / I 1 The cubic boron nitride sintered body according to claim 1 , wherein is 0.07 or more and 0.55 or less.
6. The phase containing the W element contains a Co element, 2. The cubic boron nitride sintered body according to claim 1, wherein in said phase containing W element, the content of Co element with respect to the total content of W element and Co element is 5 atomic % or more and less than 50 atomic %.
7. A cubic boron nitride sintered body according to any one of claims 1 to 6, and a coating layer formed on a surface of the cubic boron nitride sintered body, A coated cubic boron nitride sintered body, wherein the average thickness of the entire coating layer is 0.5 μm or more and 6.0 μm or less.
Citation Information
Patent Citations
Cutting tool and surface-coated cutting tool utilizing cubic crystal boron nitride based ultrahigh-pressure sintered body as tool base body
JP2014083664A
Cubic crystal boron nitride sintered body, method of producing cubic crystal boron nitride sintered body, tool and cutting tool
JP2017014084A
Cubic boron nitride sintered body and covered cubic boron nitride sintered body
JP2023030881A
cBN SINTERED MATERIAL TOOL AND COATED cBN SINTERED MATERIAL TOOL
WO2012105710A1
Cbn sintered body and cutting tool
WO2020175598A1
Cited By
Inkjet printer and printing method
EP4786189A1
Cubic boron nitride sintered body, and, tool with covered cubic boron nitride sintered body
JP2025176892A
A cubic boron nitride sintered body, and a tool having a coated cubic boron nitride sintered body.
JP7854141B2
Cubic boron nitride sintered body, method for manufacturing the same, and tool
JP7865474B1
Cubic boron nitride sintered body, method for producing same, and tool
WO2026018883A1